Buddhism’s Pedagogical Contribution to Mindfulness - Erec S Smith (Journal of the Assembly for Expanded Perspectives on Learning, 2016)
Considering the rhetorical elements in the Buddhist text “The True Aspect of All Phenomena” opens the possibility of teaching students a more mindful approach to writing.